Consumo Slow Beauty: proposição de uma escala de mensuração - Braga, Núbia Costa de Almeida (2022)
Slow beauty consumption has expanded considerably in recent years in the search for sustainability. It is considered an offshoot of the Slow movement, which advocates a new look at self-care and beauty, in the exchange of industrialized products for sustainable, natural, organic or vegan cosmetics. Previous research found some dimensions related to the consumption of sustainable cosmetics: consumption attitude, well-being, health, reference groups and perceived attributes. However, aspects such as the production of the cosmetic itself, support for the local economy, product composition and hedonic value were not addressed. Thus, this research has the general objective of proposing and validating a psychometric scale to measure slow beauty consumption. We conducted an online survey with consumers of these types of cosmetics to measure and validate the scale. For this, exploratory factor analysis and confirmatory factor analysis were performed. The results showed the identification of the localism and authenticity constructs. The health factors and the environmental issue were perceived as elements of great importance standing out naturally in the research, however, these elements were complemented by other factors such as: product quality, packaging, availability, hedonic value, among others. This study revealed theoreticalmethodological contributions, for example, it serves as a guide for future studies that aim to develop and validate new constructs; tried to fill the attitude-behavior gap in the literature on the subject and contributed to the body of literature related to slow beauty consumer behavior. In addition, it also contributes to marketers who can explore new market segmentation and positioning strategies.